2018
DOI: 10.1182/blood-2018-99-117938
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Circulating Tumor DNA Status Post-Allogeneic Hematopoietic Stem Cell Transplantation in Acute Myeloid Leukemia and Myelodysplastic Syndrome

Abstract: Background: Allogeneic hematopoietic stem cell transplantation (alloSCT) is the only curative option for patients with high risk acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). Whereas, relapse is the main event in therapeutic failure for these patients. We previously reported the utility of residual circulating tumor DNA (ctDNA) status for identifying patients with AML and MDS at high risk for relapse post myeloablative alloSCT (Nakamura et al, ASH. 2017). However, it remains to be elucidated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In AML and MDS patients after allogeneic stem cell transplant, the monitoring of ctDNA can be used to predict relapse and the presence of ctDNA at one month and three months post-transplant correlates with survival [ 65 , 66 ] . This may identify patients in whom early interventions, such as weaning of immunosuppression, may reduce relapse rates.…”
Section: Analysing Cfdna In Haematological Conditionsmentioning
confidence: 99%
“…In AML and MDS patients after allogeneic stem cell transplant, the monitoring of ctDNA can be used to predict relapse and the presence of ctDNA at one month and three months post-transplant correlates with survival [ 65 , 66 ] . This may identify patients in whom early interventions, such as weaning of immunosuppression, may reduce relapse rates.…”
Section: Analysing Cfdna In Haematological Conditionsmentioning
confidence: 99%
“…76,77 Initial efforts are already underway in AML. 78,79 While the optimal prognostic time point of MRD assessment varies slightly based on the specific regimen and other factors, most studies have shown that detectable MRD is associated with worse outcomes regardless of when it is measured. For patients treated with intensive chemotherapy in the frontline setting, we routinely assess for MRD, at a minimum, at the end of induction and consolidation.…”
Section: Practical Considerations For the Evaluation Of Measurable Rementioning
confidence: 99%